EVALUASI PROGRAM KELOMPOK USAHA BERSAMA (KUBE) DALAM MENINGKATKAN KESEJAHTERAAN EKONOMI KELUARGA MISKIN DI KECAMATAN BOJONGSARI KOTA DEPOK - Al Hilal Hamdi; Sokhivah (Journal of Research and Publication Innovation, 2024)
Joint Business Group is an effort to improve the standard of living of poor people in urban and rural areas. This study aims to determine the success of the joint business group (KUBE) program in improving the economic welfare of poor families in Bojongsari District, Depok City and the supporting and inhibiting factors. This field research uses a Qualitative Method, the informant selection technique uses the Purposive Sampling Technique. The evaluation model used in this study is the CIPP stufflebeam evaluation model and data collection is obtained from the results of Interviews, Observations, and Documentation. Data analysis is carried out through the stages of Data Reduction, Data Presentation, and Conclusion Drawing. The location of this research is at KUBE Serua Jaya, Bojongsari District. The results of this study indicate that the evaluation of the context, input, process, and product or overall can be assessed as good. The implementation and management of KUBE are in accordance with government references and policies, namely in Permensos No. 2 of 2019, and have a positive impact on the welfare of members or the community. It's just that in this study, there was a deficiency, namely the lack of maximizing online product marketing in this digital era.